2013
DOI: 10.1186/1471-2334-13-288
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of hepatitis C virus in Egypt: a systematic review and data synthesis

Abstract: BackgroundEgypt has the highest prevalence of hepatitis C virus (HCV) in the world, estimated nationally at 14.7%. Our study’s objective was to delineate the evidence on the epidemiology of HCV infection among the different population groups in Egypt, and to draw analytical inferences about the nature of HCV transmission in this country.MethodsWe conducted a systematic review of all data on HCV prevalence and incidence in Egypt following PRISMA guidelines. The main sources of data included PubMed and Embase da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
355
1
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(387 citation statements)
references
References 108 publications
22
355
1
9
Order By: Relevance
“…Our study showed increased HCV seropositivity among males (54.5%), rural areas (90.9%) and low class (63.6%), this agreed with Mohamoud et al, who reported higher HCV prevalence in males [23], also in agreement with Mostafa et al, who demonstrated higher prevalence in rural areas [24].…”
Section: Discussion:-supporting
confidence: 82%
“…Our study showed increased HCV seropositivity among males (54.5%), rural areas (90.9%) and low class (63.6%), this agreed with Mohamoud et al, who reported higher HCV prevalence in males [23], also in agreement with Mostafa et al, who demonstrated higher prevalence in rural areas [24].…”
Section: Discussion:-supporting
confidence: 82%
“…HCV prevalence in Egypt increases strongly with age and indicates uneven geographic distribution, with higher HCV prevalence in rural areas compared to urban settings [2][3][4] and in Lower Egypt compared to the rest of the country. [5,4] The cumulative data [6 -10] showed that Egypt has the largest HCV epidemic in the world and the epidemic is ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of HCV epidemic is not clear but thought to be due to the past and ongoing iatrogenic exposure [4,5] in the health-care settings. Direct percutaneous exposure to blood represented the primary route of HCV transmission from patients to healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…[3] It is now well established that HCV is a global health challenge and a leading cause of liver cirrhosis worldwide, with an estimated 130-170 million chronic infections (2-3% of the global population). [4] Measurement of portal hemodynamics can serve as an important tool in the follow-up of patients undergoing endoscopic and/or pharmacologic intervention for secondary prevention of variceal hemorrhage.…”
Section: Introductionmentioning
confidence: 99%